Glaesserella parasuis autotransporters EspP1 and EspP2 are novel IgA-specific proteases - Wang, Zhichao; Gu, Jiayun; Xiao, Kunxue; Zhu, Wenlong; Lin, Yan; Wen, Siting; He, Qigai; Xu, Xiaojuan; Cai, Xuwang (Frontiers in Microbiology, 2022)
Glaesserella parasuis causes Glässer’s disease, which is associated with severe polyarthritis, fibrinous polyserositis and meningitis, and leads to significant economic losses to the swine industry worldwide. IgA is one of the most important humoral immune factors present on mucosal surfaces, and it plays a crucial role in neutralizing and removing pathogens. G. parasuis is able to colonize the mucosal membrane of respiratory tract without being eliminated. Nevertheless, the immune evasion mechanism of G. parasuis in thwarting IgA remains unclear. The object of this study was to characterize the IgA degradation activity of Mac-1-containing autotransporters EspP1 and EspP2 in G. parasuis. We report for the first time that both EspP1 and EspP2 have the ability to cleave swine IgA. Moreover, interaction between G. parasuis mutant strains and swine IgA demonstrated that EspP1 and EspP2 are the only two IgA proteases in G. parasuis. IgA was cleaved by EspPs at three different positions within the Cα1 and Cα3 domains. The putative catalytic center of EspPs consists of cysteine, histidine and aspartate, indicating that EspP1 and EspP2 are cysteine protease rather than serine protease. Western blot analysis revealed for the first time that besides IgA, G. parasuis is also capable of degrading IgM, but EspPs are not involved. Both EspP1 and EspP2 are IgA-specific proteases, as they exclusively cleaved swine IgA, but not IgG or IgM. Altogether, our work describes a pair of novel IgA-specific proteases from G. parasuis, and provides a theoretical basis for the immune evasion process of G. parasuis.